2021
DOI: 10.3390/app11156844
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Computed Tomography Angiography Protocols for Follow-Up Type B Aortic Dissection Patients by Using 3D Printed Model

Abstract: Thoracic endovascular aortic repair (TEVAR) is a life-saving therapy for type B aortic dissection (TBAD). However, surveillance computed tomography (CT) scans in post-TEVAR patients are associated with high radiation dose, thus resulting in potential risk of radiation-induced malignancy. In this study, we developed a patient-specific three-dimensional (3D) printed phantom with stent grafts in situ, then scanned the phantom with different CT protocols to determine the optimal scanning parameters for post-treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…In previous studies, TangoPlus FLX930, TangoGray TM and TangoBlack TM (Stratasys) are reported to produce 3D printed heart and vascular models with soft and elastic features [ 24 ]. Recent research has shown that Visijet CE-NT (3D Systems Inc., Wilsonville, OR, USA) has the same tissue properties as cardiac tissues with similar CT attenuation; thus, it is more suitable for the 3D printed heart and vascular models ( Figure 3 ) [ 25 ].…”
Section: 3d Printers and Printing Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous studies, TangoPlus FLX930, TangoGray TM and TangoBlack TM (Stratasys) are reported to produce 3D printed heart and vascular models with soft and elastic features [ 24 ]. Recent research has shown that Visijet CE-NT (3D Systems Inc., Wilsonville, OR, USA) has the same tissue properties as cardiac tissues with similar CT attenuation; thus, it is more suitable for the 3D printed heart and vascular models ( Figure 3 ) [ 25 ].…”
Section: 3d Printers and Printing Materialsmentioning
confidence: 99%
“…Printing materials have an impact on the user’s performance when performing a simulation of interventional procedures as 3D models printed with soft and elastic materials allow the user to acquire a similar tactile experience to human vascular tissue, and this is especially important for structures like vessels and cardiac valves as highlighted in some studies [ 64 , 65 ]. Current developments in 3D printing technologies and printing materials have enabled achieving this goal with the selection of appropriate materials to replicate human cardiovascular tissue properties [ 25 , 70 ]. Evidence strongly recommends that 3D printed vascular models serve as a valuable tool for simulating and rehearsing cardiac or interventional radiology procedures.…”
Section: Clinical Applications Of 3d Printed Models In Cardiovascular...mentioning
confidence: 99%
See 3 more Smart Citations